TINJAUAN KUAT LENTUR BALOK PADA BETON MUTU TINGGI DENGAN MENGGUNAAN WASTE CONCRETE - Ahmad Hamidi; Sjelly Haniza; M. Ardi Idris (Universitas Trisakti, 2021)
The use of reinforced concrete as a building material has become one of the solutions to get a strong and sturdy building. The use of reinforced concrete is considered to have strength in resisting compressive and tensile forces. Besides, concrete can be used according to the quality level required during the construction process. The use of concrete sometimes results in waste concrete such as used pile fragments, broken concrete from building repairs, or from tests in the laboratory. If waste concrete is not utilized, it will become an environmental problem in the future. The existence of waste concrete if it is utilized will be able to provide economic value and can reduce the occurrence of environmental problems, one of which is the use of waste concrete from broken electric poles from one of the producers. This waste concrete is the result of testing electric poles before being distributed to the owner. The fragments of electricity pile waste concrete can be used as a substitute for some of the coarse aggregate in high strength concrete. The waste concrete is cracked first and the granules used are those that pass the 30 mm sieve with a percentage of 20% of the total coarse aggregate. To get good workability, a superplasticizer is used as an added ingredient. The variation in the use of the superplasticizer is 0%; 0.5%; 1% and 1.5%. The flexural strength test was carried out at the age of 28 days with the results of the average compressive strength for 0% variation of 3.2 MPa, 0.5% variation of 3.69 MPa, 1% variation of 4.67 MPa, and 1.5% variation amounting to 5.02 MPa with the percentage rate of increase from normal concrete successively of 15.28%; 39.76% and 39.05%.